Croma k. Per una tendenza della poesia contemporanea (ENTHYMEMA, 2020)
This article considers the first nine books from the series Croma k (Oèdipus publishing house). The aim of the article is to link the formal aspects of these works with a possible trend of the contemporary Italian poetry.
Keywords: Corma K; Contemporary Italian Poetry; Ivan Schiavone; Oèdipus; History of publishing